The Influence of Compensation and Work Environment on Employee Performance - Ihsan, Ibnu Syawqy; Widagdo, Bambang; Novianti, Khusnul Rofida (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This research aims to determine the effect of compensation and work environment on employee performance at PT. Gracia Optima Masterpro. This research uses quantitative methods with a descriptive approach. The analytical method used is multiple linear regression analysis using SPSS 25. The population in this research is employees of PT. Gracia Optima Masterpro with a sample of 97 respondents using a total sampling approach. The results of this research are that if compensation has a high value, the work environment is in good condition and employee performance has a high value, then compensation has a significant positive effect on employee performance, the work environment has a significant positive effect on employee performance and compensation and the work environment have a significant positive effect on employee performance.